A study of anal intraepithelial neoplasia in HIV positive homosexual men. Issue 3 (1st June 1999) - Lacey, H B; Wilson, G E; Tilston, P; Wilkins, E G; Bailey, A S; Corbitt, G; Green, P M
Abstract : OBJECTIVES: To determine the prevalence of high grade anal intraepithelial neoplasia (HGAIN), the value of anal cytology in screening for HGAIN, and the characterisation of epidemiological factors and human papillomavirus (HPV) types. METHODS: Prospective cohort study of HIV positive homosexual men. Subjects were interviewed, underwent STD, anal cytological, and HPV screening at enrolment and at subsequent follow up visits with anoscopy and biopsy at the final visit. 57 enrolled, average CD4 count 273 x 10(6)/l (10-588); 41 completed the cytological surveillance over the follow up period (181 visits, average follow up 17 months), 38 of these had anoscopy and anal biopsy. RESULTS: Oncogenic HPV types were detected in 84% and high grade dyskaryosis in 10.5% (6/57) at enrollment. There was a 70% incidence of high grade dyskaryosis during follow up in patients with negative/warty or low grade dyskaryosis at enrollment. Anoscopy correlated with histology in high grade AIN lesions (sensitivity 91%, specificity 54%) and cytology was 78% sensitive (18/23) for HGAIN on biopsy. CONCLUSIONS: AIN and infection with multiple oncogenic HPV types are very common among immunosuppressed HIV positive homosexual men. Apparent progression from low to high grade cytological changes occurred over a short follow up period, with no cases of carcinoma. All 23 cases of HGAIN were predicted by cytology and/or anoscopy. Future studies focusing on the risk of progression to carcinoma are needed before applying anal cytology as a screening tool for AIN in this population.